The precariousness of parents and its influence on their children's academic performance at the secondary level (Revista Innova Educación, 2025)
In an increasingly globalized world, job insecurity has increased in Latin America, affecting levels of social well-being. As a result, many families are trapped in a cycle of poverty from which it is difficult to escape. In this context, education becomes a key tool for improving quality of life. The objective of this study is to analyze the influence of parents' precarious employment conditions on their children's academic performance, with a particular focus on schools in the outskirts of Mazatlán, Sinaloa. Methodology: The study was exploratory in-depth with a qualitative approach, using a case study method. Data collection techniques included semi-structured interviews. Results: Although parents value educational attainment and have expectations about their children's future employment, their perceptions are driven by their own precarious employment experiences. In conclusion, a relationship was identified between parents' precarious employment conditions and students' poor academic performance. These findings highlight the need for a multidisciplinary approach to addressing educational issues from a social perspective that considers the structural conditions that impact academic performance.
Keywords: academic performance; family; inequality; job insecurity